Polystichum neoacutidens (subg. Haplopolystichum; Dryopteridaceae), a new fern from northeastern Thailand - Pollawatn, Rossarin; Zhang, Liang; Limpanasittichai, Ponpipat; Zhang, Li-Bing (Phytotaxa, 2020)
A new fern species, Polystichum neoacutidens (Dryopteridaceae), is described and illustrated from a limestone area in northeastern Thailand. It is distinguished from its closest relative, P. acutidens, by the color of petioles and rachises, density of petiole scales, and position of sori.